Analytical Methods in Supramolecular Chemistry, 2nd, Completely Revised and Enlarged Edition - Schalley, Christoph (Wiley-VCH Verlag & Co. KGaA, 2012)
An overview of the techniques used to examine supramolecular aggregates from a methodological point of view. Edited by a rising star in the community and an experienced author, this is a definitive survey of useful modern analytical methods for understanding supramolecular chemistry, from NMR to single-molecule spectroscopy, from electron microscopy to extraction methods. A definitive study of this field touching many interdisciplinary areas such as molecular devices, biology, bioorganic chemistry, material science, and nanotechnology.